Logoterapia e orientação espiritual: a pessoa em condição de sofrimento inevitável - de Andrade, Aíla Luzia Pinheiro (Kairós: Revista Acadêmica da Prainha, 2021)
Postmodernity has been characterized by ephemerality and evanescence of life experience. However, many people live durable experience inevitable suffering and empty meaning in life. Viktor Frankl established the Logoterapia as psychotherapy of sense of life. Both Logoterapia and the practice of Spiritual Guidance (pastoral care) aim to make people aware that even when life does not seem to make any sense, yet there is a sense that transcends all human experience. This research aims to find an interface between Logotherapy and Spiritual Guidance to the pastoral goal of helping people living in inevitable suffering.